INTEGRASI MSDI DAN CSR: STRATEGI MEMBANGUN ORGANISASI BERKELANJUTAN DI ERA MODERN - jazilar rohman, Muhammad faqih; Rini Puji Astuti; Indah Nurul Hidayati; Putri Sofiatul Islamiah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2025)
This study aims to analyze the relationship between Human Resource Management (HRM) and Corporate Social Responsibility (CSR) in realizing organizational sustainability in the modern era. The integration of HRM and CSR is an important strategy in building a company that is not only profit-oriented, but also social welfare and moral values. HRM plays a role in managing human resources based on Islamic principles such as amanah (trust), ihsan (goodness), and maslahah (benefit), which can encourage ethical and fair work behavior. The results of the study indicate that the synergy between HRM and CSR can increase employee loyalty, productivity, and a positive company image in the public eye. Thus, the integration of these two concepts plays a crucial role in creating a highly competitive, ethical organization that contributes to sustainable economic development based on Islamic values